Optical Characteristics of Metasurfaces at Meta-Atom Anapole - Kang Du; Pei Li; Qiwei Miao; Kun Gao; Heng Wang; Lixun Sun; Wending Zhang; Ting Mei (IEEE Photonics Journal)
Optical characteristics of square-latticed metasurfaces are analyzed by equations derived from a dipole-quadrupole system. For the metasurface composed of Si nanospheres, meta-atoms maintain the anapole characteristics of the single scatterer, which are not affected by the lattice period. The far-field response of the metasurface thus can be engineered without significantly disturbing near-fields in meta-atoms. In addition, as exhibited with Ag/Si core–shell nanospheres, the transmittance of metasurface at anapole can also be modulated and even nulled by shifting the lattice magnetic dipole and quadrupole resonances. In a small-period metasurface, the near-field interaction of adjacent meta-atoms manipulates the lattice resonance behavior, leading to significant modulation in transmittance at anapole.